Mechanical, barrier, thermal, and microstructural properties of poly (lactic acid) and gelatin–beeswax emulsion bi-layer films - Pirinç, Fatma Tuba; Dağdelen, Adnan Fatih; Sarıcaoğlu, Furkan Türker (John Wiley and Sons Inc, 2021)
In this study, biodegradable bi-layer films from poly (lactic acid) (PLA) and bovine gelatin (BG)–beeswax emulsion were produced. PLA film was used as first layer, while BG containing beeswax at 0, 0.25, 0.50, 0.75, and 1% was the second layer, and optical, mechanical, barrier, thermal, and microstructural properties were characterized. The increasing beeswax concentration significantly increased the color difference (ΔE) and opacity of films, whereas decreased the light transmittance. Although tensile strength (TS) values decreased with the addition of beeswax, elongation at break (EAB) values increased. The highest oxygen permeability was observed from PLA film and production of bi-layer film significantly decreased the oxygen permeability. Microstructural images of bi-layer films containing 0.25 and 0.50% beeswax had good compatibility; however, increasing beeswax concentration to 0.75 and 1% weakened the interfacial adhesion of layers. PLA coated with BG–beeswax emulsions enhances the suitability of PLA films for food packaging applications. Novelty impact statement: Poly (lactic acid) film was coated with gelatin–beeswax emulsion films to produce bi-layer films with low oxygen permeability. Gelatin–beeswax emulsion as outer layer improved the oxygen barrier properties of inner PLA layer. The production of PLA–gelatin/beeswax emulsion bi-layer films could be valuable for food packaging applications due to low water vapor and oxygen permeability.
Keywords: Food products; Mammals; Colorimetry; Tensile strength; Oxygen permeable; Food packaging; Poly lactic acid